A Study of Liked/Disliked Television Commercials in India - Fam, Kim Shyan; Waller, David S. (Indian Journal of Marketing, 2008)
This study analyzes consumers’ attitudes towards television commercials using telephone interviews in Mumbai to provide an insight into the constructs of "advertising likeability" and "advertising dislikeability". While there have been a number of studies which have emphasized the role of ’liking’ a commercial as an important evaluative measurement, few studies have observed the what factors cause the ’liking’ and ’disliking’ of an advertisement in India. The findings raise some issues for those advertising in the Indian marketplace.